Fatores associados à doença periodontal em gestantes em uma unidade de saúde da família de Salvador/BA - Leite, Érica Brazil (2023)
Pregnancy is a delicate period for women, a time that causes a series of changes to develop in them from a social/psychological and physical/biological point of view. Changes occur as the body seeks a balance with the aim of generating life and maintaining maternal health in good condition. In the mouth, the main changes create conditions favorable to the onset or worsening of periodontal disease. Furthermore, external factors are often associated with an increased incidence of periodontal disease during pregnancy. The presence of this condition during pregnancy is related to the occurrence of premature births and low birth weight. This research aimed to estimate the prevalence of periodontal disease in pregnant women and determine factors associated with the disease in all pregnant women at the Family Health Unit (USF) of Canabrava in the city of Salvador/BA. Through an observational, cross-sectional study, data collection was carried out between December 2022 and May 2023 and involved signing the Free and Informed Consent Form, completing the questionnaire, evaluating the pregnant woman's booklet and carrying out oral and periodontal examinations. The independent variables analyzed were described as sociodemographic, general clinical conditions, oral conditions and access to health services for the pregnant woman. After analyzing the data, a prevalence of 30.77% for periodontal disease was found, according to the criteria proposed by Gomes-Filho et al. (2018), in which 60.00% were considered severe periodontitis; 35% with moderate periodontitis, 5% with mild periodontitis. The crude and adjusted association measures revealed the absence of a statistically significant association between periodontal disease and the variables analyzed. The main results of this study suggest that there is no positive association between periodontal disease and the variables investigated. However, thehigh prevalence of severe periodontitis in the sample highlights the urgent need to implement public policies to deal with this condition that has a major impact on the health of pregnant women and possible negative outcomes for the baby